Risk factors and preventive measures for abnormal blood pressure during hemodialysis filtration for patients with sepsis - Zhang Chunfang; Lin Tingting; Xia Yu; Zhang Daowei (Vojnosanitetski Pregled)
Background/Aim. Hemodialysis filtration (HDF) plays an extremely important role in treating patients with sepsis and subsequent acute renal failure. However, abnormal blood pressure (ABP) during HDF badly influences the prognosis and increases all-cause mortality in patients with sepsis. The aim of the study was to investigate risk factors and preventive measures of ABP during HDF for patients with sepsis. Methods. A total of 145 patients with sepsis undergoing HDF were included in this study, and they were divided into two groups: the normal blood pressure (NBP) group (n = 89) and the ABP group (n = 56). Their clinical data were collected, and the independent influencing factors for ABP during HDF were assessed by univariate and multivariate logistic regression analyses. A nomogram model for prediction was constructed based on the results of multivariate analysis, and its discrimination and consistency were assessed using receiver operating characteristic and calibration curves. The Kaplan-Meier method was used to plot the survival curve to evaluate the prognosis 28 days after HDF. Results. Multivariate logistic regression analysis revealed that age, blood calcium, fasting plasma glucose, intact parathyroid hormone, ultrafiltration volume, and ultrafiltration rate were independent risk factors, whereas albumin was a protective factor for ABP during HDF (p < 0.05). The nomogram model exhibited a good fitting effect, with high discrimination and accuracy. Kaplan-Meier survival analysis showed that the NBP group had a significantly higher 28- day survival rate than that of ABP (88.76% vs. 73.21%) (p < 0.05). Conclusion. The constructed risk model is suitable for identifying high-risk groups and provides a reference for effective prevention and treatment, to lower the incidence rate of ABP and improve the prognosis.